2003
DOI: 10.1094/phyto.2003.93.11.1378
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Pathotypes and DNA Fingerprint Haplotypes in Populations of Magnaporthe grisea in Korea over Two Decades

Abstract: Using isolates collected over 2 decades, we determined the population structure and dynamics of the rice blast fungus, Magnaporthe grisea, in Korea at both the genotypic and phenotypic levels. Pathotype analysis on 6,315 isolates collected from 328 rice cultivars from 1981 to 2000 revealed the presence of a total of 91 pathotypes. Among these 91 patho-types, nine dominated, comprising 76.5% of the isolates. The expected number of pathotypes (corrected for sample size) increased significantly during the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…Studies on genetic structure of P. grisea population using MGR-DNA fingerprinting showed that even though each isolate had a unique fingerprint, they could be grouped into distinct lineages The results of the analysis of isolates from Primavera and Maravilha using rep-PCR in the present study are in accordance with the observations made in earlier investigations (Levy et al, 1991;Levy et al, 1993;Xia et al, 1993;Chen et al, 1995;Roumen et al, 1997;Don et al, 1999;Park et al, 2003;Rathour et al, 2004). Information on the interactions between cultivars and lineages can be used to improve the diversity of pathogen populations at screening sites .…”
Section: Virulence (%)supporting
confidence: 92%
See 1 more Smart Citation
“…Studies on genetic structure of P. grisea population using MGR-DNA fingerprinting showed that even though each isolate had a unique fingerprint, they could be grouped into distinct lineages The results of the analysis of isolates from Primavera and Maravilha using rep-PCR in the present study are in accordance with the observations made in earlier investigations (Levy et al, 1991;Levy et al, 1993;Xia et al, 1993;Chen et al, 1995;Roumen et al, 1997;Don et al, 1999;Park et al, 2003;Rathour et al, 2004). Information on the interactions between cultivars and lineages can be used to improve the diversity of pathogen populations at screening sites .…”
Section: Virulence (%)supporting
confidence: 92%
“…Distinct DNA fingerprint groups or lineages were identified using the probe MGR586 (Filippi et al, 1999;Hamer, 1991;Zeigler et al, 1995). Many of these clonal lineages have been shown to exhibit restricted diversity (Levy et al, 1993;Xia et al, 1993;Chen et al, 1995;Roumen et al, 1997;Don et al, 1999;Park et al, 2003;Rathour et al, 2004). Because of difficulties in large scale use of RFLP analysis, a rep-PCR technique with two primer sequences from Pot2 has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of RAPD analysis showed quite good congruence with the results obtained from ISSR studies, a greater effective ratio of multi-locus Table 1 Coefficient doi: 10.17221/102/2016-CJGPB markers as well as a higher number of private alleles were observed using ISSR markers (Nasehi et al 2014). (Mishra et al 2006), Korea (Park et al 2003), China (Ngueko et al 2004), Iran (Javan-Nikkhah et al 2004 and India (Chadha & Gopalakrishna 2005), which is in agreement with the findings of this study. To the best of our knowledge, this is the first report on the genetic diversity of M. oryzae isolates using ISSR and RAPD markers in Malaysia, and evaluating these two types of markers to differentiate rice blast pathogen populations.…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, continuous genotypic variation and lack of association between genetic and virulence patterns was observed in other countries (Mekwatanakarn et al, 2000;Park et al, 2003;Rathour et al, 2004). Observations from different countries indicate the possibility of genetic recombination in the pathogen population.…”
Section: Coefficientmentioning
confidence: 98%
“…In Korea, the genetic analysis of 176 isolates of M. oryzae collected in farmers' fields and nurseries did not show a well defined lineage structure (Park et al, 2003). Rathour et al (2004), in the northwestern Himalyan region of India, also showed the presence of high genetic diversity and continuous variation in 48 isolates, using RAPD markers.…”
Section: Introducionmentioning
confidence: 93%